Organization of Highly Acetylated Chromatin around Sites of Heterogeneous Nuclear RNA Accumulation - Hendzel, Michael J. (The American Society for Cell Biology, 1998)
Histones found within transcriptionally competent and active regions of the genome are highly acetylated. Moreover, these highly acetylated histones have very short half-lives. Thus, both histone acetyltransferases and histone deacetylases must enrich within or near these euchromatic regions of the interphase chromatids. Using an antibody specific for highly acetylated histone H3, we have investigated the organization of transcriptionally active and competent chromatin as well as nuclear histone acetyltransferase and deacetylase activities. We observe an exclusion of highly acetylated chromatin around the periphery of the nucleus and an enrichment near interchromatin granule clusters (IGCs). The highly acetylated chromatin is found in foci that may reflect the organization of highly acetylated chromatin into “chromonema” fibers. Transmission electron microscopy of Indian muntjac fibroblast cell nuclei indicates that the chromatin associated with the periphery of IGCs remains relatively condensed, most commonly found in domains containing chromatin folded beyond 30 nm. Using electron spectroscopic imaging, we demonstrate that IGCs are clusters of ribonucleoprotein particles. The individual granules comprise RNA-rich fibrils or globular regions that fold into individual granules. Quantitative analysis of individual granules indicates that they contain variable amounts of RNA estimated between 1.5 and >10 kb. We propose that interchromatin granules are heterogeneous nuclear RNA-containing particles, some of which may be pre-mRNA generated by nearby transcribed chromatin. An intermediary zone between the IGC and surrounding chromatin is described that contains factors with the potential to provide specificity to the localization of sequences near IGCs.